Self-reported use and clinical usefulness of second-generation decision support - a survey at the pilot sites for Evidence-Based Medicine elec-tronic Decision Support (EBMeDS) - Tiina Kortteisto; Minna Kaila; Ilkka Kunnamo; Peter Nyberg; Anna-Mari Aalto; Pekka Rissanen (Finnish Social and Health Informatics Association, 2009)
In Finland, electronic decision support is evolving from searchable knowledge bases toward integration of the knowledge modules into the electronic health record in the Evidence-Based Medicine electronic Decision Support project. We conducted a baseline survey on the extent of use of second-generation decision support (electronic databases) by the various categories of health care professionals. The results showed that the majority of health care professionals used the electronic databases in their clinical practice; more than 80% of participating physicians, registered nurses, public health nurses, and ward nurses used at least four databases. In addition, the respondents considered these databases clinical useful in their practice. This indicates that health care professionals seem to be ready for the third-generation clinical decision support system, producing, for example, automatic reminders.